Using the Ranked Discrepancy Model to Identify Priority Topics for Professional Development for Agricultural Extension - Lendel K. Narine (Journal of International Agricultural and Extension Education, 2024)
In an ever-changing agricultural context, extension agents are expected to possess the competencies to provide relevant non-formal education to their clientele on persistent and emerging issues. This research note applies the Ranked Discrepancy Model (RDM) to assess priority topic areas for professional development activities in agricultural extension. The study followed a correlation design and gathered survey data from a sample of agricultural extension agents at [University] (n = 42). Results indicated the high priority areas for professional development irrigation technologies, weed control, post-farm activities (e.g., value-added products and marketing), and GPS technologies and drones for real-time monitoring. The study also showed the simplicity of the RDM in handling repeated-measures data, as the analysis was performed entirely in Microsoft Excel. The research note provides a replicable framework for researchers examining agents' professional development needs.
Keywords: Needs assessment; professional development; competency; education